RCMP Officers Posted to Nunavut Communities: Exploring the Policing and Private Life Challenges of Qallunaat Police in Inuit Nunangat ... - Hamel-Touchette, Sophie (Université d'Ottawa | University of Ottawa, 2025)
As a result of a signed agreement between the Government of Canada and Nunavut, the Royal Canadian Mounted Police (RCMP) is contracted to police Nunavut hamlets. This iteration of contracts began when the Territory was formed in 1999 and involves the recruitment of Regular Members from across Canada. To better understand the experiences of these Members, this thesis project engages with the literature on rural and remote policing, and explores the uniqueness of policing in Nunavut (Ruddell & Jones, 2018). Inspired by informal Member comments about the “harsh reality” of these posts, this project investigates accounts of everyday policing in several hamlets. Through a qualitative approach, specifically semi-structured interviews, and framed by Settler Colonialism theory and Bourdieu's theory on Habitus, this project applies “policing habitus” to understand the daily living and working conditions of police officers in Nunavut. The analysis shows that officers identify a number of obstacles in their “field” ...